Digital Goods Are Valued Less Than Physical Goods - Atasoy, Ozgun; Morewedge, Carey K (Journal of Consumer Research, 2018)
Abstract Digital goods are, in many cases, substantive innovations relative to their physical counterparts. Yet, in five experiments, people ascribed less value to digital than to physical versions of the same good. Research participants paid more for, were willing to pay more for, and were more likely to purchase physical goods than equivalent digital goods, including souvenir photographs, books (fiction and nonfiction), and films. Participants valued physical goods more than digital goods whether their value was elicited in an incentive compatible pay-what-you-want paradigm, with willingness to pay, or with purchase intention. Greater capacity for physical than digital goods to garner an association with the self (i.e., psychological ownership) underlies the greater value ascribed to physical goods. Differences in psychological ownership for physical and digital goods mediated the difference in their value. Experimentally manipulating antecedents and consequents of psychological ownership (i.e., expected ownership, identity relevance, perceived control) bounded this effect, and moderated the mediating role of psychological ownership. The findings show how features of objects influence their capacity to garner psychological ownership before they are acquired, and provide theoretical and practical insights for the marketing, psychology, and economics of digital and physical goods.